An efficient approach of improving privacy and security in online social networks. (4th August 2017) - Almasoud, Suliman K.; Almogren, Ahmad; Hassan, Mohammad Mehedi; Alrassan, Iehab
Summary: Online social networks (OSNs) have become popular and widely used by many people nowadays. As those OSNs increase, the virtual social interactions have resulted in increasing privacy and security concern. Many approaches have been proposed in order to provide users with "better" privacy protection, but none of those approaches have "fully succeeded, " due to their conflict with service providers' economic benefits or due to the suggestion of changing the OSNs architecture. In this paper, we propose a new model that would improve privacy and security in OSNs by preventing users from revealing private and or confidential information online as possible. We endeavor to create a balance between privacy and security improvement versus the service provider business model.